The Imperial Mode of Living in a semi-peripheral social formation: notes on the case of Brazil - Theis, Ivo M. (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
Contrasting images, arising from disparate, if not opposed, diagnoses disseminated over the last two centuries by representatives of different sectors of Brazilian society, raise the question of how the “imperial mode of living” manifests itself in Brazil. The imperial mode of living approach can be considered a construct that proposes to explain everyday life as being conditioned by the social relations prevailing under the dominance of neoliberal globalization, including the relations between society and environment. The main purpose of this article is to mobilize evidence and offer a plausible answer to that question. The analysis of the historical process of formation and of the socio-spatial contradictions of Brazilian development suggests that, from the perspective of the ruling classes, and of a considerable part of the intelligentsia and even of the progressive political forces, the vision of the future of Brazil seems to converge with the premises of the “imperial mode of living”. From the perspective of the subalternized classes, the options indicate autonomy, social self-regulation and social self-determination – which point to the authentic Novum.